Exploration of Scientific Literacy in Indonesian Language Textbooks for Elementary and Secondary School - Mahyudi, Johan; Mahsun, Mahsun; Sukri, Sukri; Sirulhaq, Ahmad; Musaddat, Syaiful; Hijriah, B. Siti (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2023)
This study aims to explore scientific literacy in Indonesian language textbooks at the elementary and secondary school levels. The explorative qualitative method was applied in this study. The data was collected through explanation materials, procedural writings, scientific papers, exposition texts, and review texts from Indonesian language textbooks for elementary and middle school students. This study’s data analysis technique was content analysis. The data was analyzed to confirm its suitability with the type of text represented and then validated for its role in supporting scientific literacy. The results of the research showed that (1) not all sample texts met the basic criteria as appropriate teaching materials; (2) if the text met the criteria as an example text of teaching materials, the text did not contain aspects of scientific literacy; and (3) of all the texts examined, only explanatory texts for elementary level students contained scientific literacy content in addition to meeting the criteria as sample texts of teaching materials. Based on these findings, Indonesian language textbook compilers should be more cautious in selecting samples of texts that will be discussed collaboratively by teachers and students.